“Last Hired, First Fired”: The Effect of the Unemployment Rate on the Probability of Repeat Offending - D’Alessio, Stewart J. (American journal of criminal justice, 2014)
Research examining the connection between the unemployment rate and the aggregate crime is inconclusive. One explanation for the inconsistent findings is that the unemployment rate influences the criminal activity of repeat and first-time offenders in different ways. Results support this thesis by revealing an inverted U-shaped association between the unemployment rate and the probability of repeat offending. The curvilinear relationship likely results from repeat offenders and those lacking a criminal record entering and exiting the labor force at different levels of unemployment. Our findings highlight the role that the unemployment rate plays in affecting repeat offending and underscore the importance of distinguishing between repeat and first-time offending when analyzing the effect of the unemployment rate on crime.